Clinical Significance of International Union Against Cancer pN Staging and Lymph Node Ratio in Node-Positive Colorectal Cancer after Advanced Lymph Node Dissection. Issue 5 (May 2016) - Märkl, Bruno; Olbrich, Georg; Schenkirsch, Gerhard; Kretsinger, Hallie; Kriening, Bernadette; Anthuber, Matthias
Abstract : BACKGROUND: Lymph node retrieval in colorectal cancer can be improved by using advanced histopathological techniques like methylene blue-assisted lymph node dissection, which results in a doubling or even tripling of the lymph node count in comparison with conventional lymph node dissection techniques. However, it is not clear whether the established lymph node staging systems are suitable for predicting patients' prognoses under these circumstances. OBJECTIVE: The aim of this study was to determine whether the current lymph node staging systems are suitable when advanced dissection methods are used. DESIGN: This is a retrospective cohort study. SETTING AND PATIENTS: We formed a study group (methylene blue-assisted lymph node dissection) of 293 patients and a control group (conventional lymph node dissection) of 232 patients, each with node-positive cases. Conventional pN staging according to the International Union Against Cancer, seventh edition, and lymph node ratio were applied. MAIN OUTCOME MEASURES: Overall survival was compared by using the different staging systems in a uni- and multivariable fashion. RESULTS: The lymph node ratio values were reduced in the advanced methylene blue-assisted lymph node dissection group in comparison with the conventional lymph node dissection group (0.1 vs 0.3, p < 0.001). Although pN staging proved to be reliable, the cutoff values for lymph node ratio staging had to be adapted. The new cutoffs (0.07, 0.15, and 0.34) were prognostic. However, multivariable analysis revealed pN staging and vascular invasion, but not lymph node ratio, as independently prognostic in the methylene blue-assisted lymph node dissection group. LIMITATIONS: The study group and historical control group are not perfectly balanced because the case number in the stage III subgroup of the control group is small. CONCLUSIONS: pN staging proved to be a robust prognostic marker in colorectal cancer under the circumstances of improved lymph node harvest. After adaptation of the cutoff values, lymph node ratio is also prognostic but not superior to pN staging.